Selected Physical, Colour and Textural Characteristics of Market Rasogolla - K., Srinivasa; Barnwal, Pradyuman; Singh, Pritpal (Indian Journal of Dairy Science, 2017)
Rasogolla is regarded as the king of Indian milk sweets. The various characteristics such as physical (size, unit weight, juiciness and porosity), colour and textural quality characteristics of Rasogolla plays a vital role in its marketing and consumer acceptance. In present study, physical, colour and textural quality characteristics of six brands of market Rasogolla were determined. The size, geometric mean diameter, varied from 2.7±0.0 mm to 3.9±0.1 cm. All physical and colour characteristics of market Rasogolla were found statistically highly significant (p<0.001) with sample type (brand). The cohesiveness, hardness, springiness, gumminess and chewiness were found statistically highly significant (p<0.001) whereas fracturability was found statistically moderately significant (p<0.05) with sample type (brand). Unit weight, juiciness and porosity (minimum to maximum) varied from 15.742±0.907 g to 43.352±1.331 g, 44.3±0.3 % to 64.4±0.1 % and 5.5±1.1 % to 50.8±1.9 %, respectively. The values of L*, a*, b* and hue angle ranged (minimum to maximum) between 57.40 ± 2.61 to 74.21 ± 0.87, -2.54 ± 0.18 to -0.99 ± 0.19, 7.25 ± 0.94 to 12.45 ± 0.45 and -83.56º ± 0.89 to -70.43º ± 3.37, respectively. The average values for cohesiveness, fracturability, hardness, springiness, gumminess and chewiness ranged (minimum to maximum) between 0.31±0.03 to 0.68±0.02, 64.96±5.60 to 100.47±5.73 N, 81.30±5.25 to 144.31±8.66 N, 0.44±0.02 to 0.92±0.01, 33.65±0.89 to 64.24±10.86 N and 14.62±0.33 to 58.07±10.20 N, respectively. Size of Rasogolla plays a vital role for market acceptance along with other characteristics for development of process equipments for Rasogolla cooking.